Estudo comparativo de precursores da PpIX (ALA e MAL) utilizados topicamente em terapia fotodinâmica - Rego, Raquel Ferreira (Universidade Federal de São Carlos, 2008)
Photodynamic therapy (PDT) is a modality for treatment of tumors, and uses a combination of a drug (photosensitizer) and light in the presence of the molecular oxygen to selectively damage target tissue. In the absent of one of these components, the cytotoxic effect is not observed. Since 1990, many works in the literature studies the topical application of precursors of protoporphyrin IX (PpIX) in PDT, such 5- aminolevulinic acid (ALA) and methyl aminolevulinate (MAL). The purpose of this work was realized an comparative study in vivo between two commercial and available drugs precursors of PpIX, the ALAsense (5-aminolevulinic acid - ALA) from Russian and Metvix (methyl aminolevulinate MAL) from United Kingdom. Experiments were carried out in animals to analyze the performance and the ALA photodynamic MAL in liver of rats. The fluorescence spectra of the liver were collected at pre-determined time. The time of accumulation of PpIX was observed by 2 hours and 45 minutes for the ALA and MAL for 4 hours after application of drugs in the liver. The formation, accumulation and depth of penetration of PpIX in liver tissue were determined by fluorescence spectroscopy. Using a total of 21 animals were the irradiation of the liver fotossensibilizado with ALA or MAL alone with different doses of light (20, 50, 100 and 200J/cm2) or in a combination MAL + ALA to 8%, 16% and 32 dose of 100J/cm2. Thirty hours after the lighting, the animals were killed and livers removed. The area of necrosis of the liver was assessed macroscopically and the samples were prepared for histological study, considering especially the aspects and depth of necrosis. In histological analysis were carried out many aspects of necrosis and the normal liver. The depths of necrosis were measured and the threshold dose obtained using a mathematical model proposed in the literature. Moreover, the monitoring was carried out of O2 consumption of mitochondria isolated from livers of rats, after topical administration of drugs precursors of PpIX (ALA and MAL) in order to check the influence of these substances in mitochondrial bioenergetics. The results showed a higher penetration of MAL in the tissue, as well as greater depth of necrosis when compared to the ALA. These results suggest that MAL has a tendency to better photodynamic response than ALA to the criteria studied.
Keywords: Terapia fotodinâmica; Protoporfirina; Ácido aminolevulínico; Metil aminolevulinato; Necrose; Tecido hepático; TFD; ALA; MAL; Aplicação tópica; Fígado; PDT; Topical application; Necrosis; Liver; OUTROS